Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(5x-16=40+x\)
\(\Leftrightarrow5x=40+x+16\)
\(\Leftrightarrow5x=x+56\)
\(\Leftrightarrow5x-x=56\)
\(\Leftrightarrow4x=56\)
\(\Leftrightarrow x=14\)
Vậy \(x=14\)
\(5x-7=-21-2x\)
\(\Leftrightarrow5x-7+21=-2x\)
\(\Leftrightarrow5x+14=-2x\)
\(\Leftrightarrow-2x-5x=14\)
\(\Leftrightarrow-7x=14\)
\(\Leftrightarrow x=-2\)
Vậy \(x=-2\)
a, x+8 chia hết cho x+7
=>x+7+1 chia hết cho x+7
=>1 chia hết cho x+7
=> x+7=1hoặc -1
=>x=(-6) hoặc (-8)
b, 2x+16 chia hết cho x+7
2(x+7)+2 chia hết cho x+7
.....
c,mọi số x
d,6 ,4
d,2,0,-2,-4
click dúng nhớ
5x+7 chia hết cho 2x+1
=> 2(5x+7) - 5(2x+1) chia hết cho 2x+1
=> (10x+14)- (10x+5) chia hết cho 2x+1
=> 10x +14 - 10x +5 chia hết cho 2x+1
=> 19 chia hết cho 2x+1
=> 2x+1 thuộc 1;-1;19;-19
=> x thuộc 0;-1;9;-10
(x+8) chia hết (x+7)
x+8-x-7chia hết (x+7)
1 chia hết (x+7)
(x+7) thuộc Ư(1)={-1;1}
x thuộc{-8;-6}
a) 2x + 3 chia hết cho x + 1
2x + 2 + 1 chia hết cho x + 1
1 chia hết cho x + 1
x + 1 thuộc U(1) = {1}
x + 1 =1< = > x = 0
Tương tự
a. 2x+3 chia hết cho x+1
=> 2x+2+1 chia hết cho x+1
=> 2.(x+1)+1 chia hết cho x+1
=> 1 chia hết cho x+1
=> x+1 \(\in\)Ư(1)={-1; 1}
=> x \(\in\){-2; 0}
b. => 4x+69 chia hết cho x+5
=> 4x+20+49 chia hết cho x+5
=> 4.(x+5)+49 chia hết cho x+5
=> 49 chia hết cho x+5
=> x+5 \(\in\)Ư(49)={-49; -7; -1; 1; 7; 49}
=> x \(\in\){-54; -12; -6; -4; 2; 44}
c. => 2x-4+11 chia hết cho x-2
=> 2.(x-2)+11 chia hết cho x-2
=> 11 chia hết cho x-2
=> x-2 E Ư(11)={-11; -1; 1; 11}
=> x E {-9; 1; 3; 13}
d. => 5x+10+18 chia hết cho x+2
=> 5.(x+2)+18 chia hết cho x+2
=> 18 chia hết cho x+2
=> x+2 E Ư(18)={-18; -9; -6; -3; -2; -1; 1; 2; 3; 6; 9; 18}
=> x E {-20; -11; -8; -5; -4; -3; -1; 0; 1; 4; 7; 16}
e. => 4x+2+17 chia hết cho 2x+1
=> 2.(2x+1) +17 chia hết cho 2x+1
=> 17 chia hết cho 2x+1
=> 2x+1 E Ư(17)={-17; -1; 1; 17}
=> x E {-9; -1; 0; 8}.
\(10x-14⋮2x+1\Leftrightarrow5\left(2x+1\right)-19⋮2x+1\)
\(\Rightarrow2x+1\inƯ\left(-19\right)=\left\{\pm1;\pm19\right\}\)